Food availability and consumption in relation to developing strategies for sustained production and supply in Nepal - Pokhrel, S. (Journal of Agriculture and Forestry University, 2020)
Nepal is classified as severe localized food insecure country with increasing import dependency ratio in each year. Relevant literatures and available data were reviewed in 2018 to find the trend of food availability and consumption in relation to developing strategies for sustained production and supply in Nepal. The per capita calories uptake is higher (2830 versus 2220 kcal) with higher in rural communities and to the richer families (4000 kcal/person/day). Whereas the protein and edible oil and fat uptake is increasing, but are yet insufficient. The diet is mostly dominated by cereals and the consumption of pulses, fruit, vegetables and animal products were comparatively lower. There is double burden of women under-nutrition (18.2%) and over-nutrition (13.5%). At present, Nepal is self sufficient only on tea, coffee, and poultry eggs. Where the import dependency ratio of fruit (88.1%), oils (83.5%) and pulses (73.4%) were very high and are in increasing trend. However, the self sufficiency ratios of cereals (97.4%), vegetables (65.9%), potato (88.8%), milk (79%), sugar (62.6%) and meat (61%) are still higher. Raising the productivity of cereals by 0.06 t/ha, vegetables 3.49 t/ha, potato/tubers 1.59 t/ha, spices 0.58 t/ ha, milk 0.30 t/head and a considerable increment of meat productivity could make the country self sufficient. Moreover, it is very hard to be self sufficient on fruit, oilseed, and fish because of their small area coverage/herd sizes, low productivity and long gestation period required. It is needed to prioritize the commodities for the allocation of production areas/heard sizes, linking all the development/infrastructure programs and output based investment for improved food production, marketing and consumption to restore national food sufficiency for livelihood support and economic resilience.